The Sequence from Invention to Innovation and its Relation to Economic Growth - Maclaurin, W. Rupert (Quarterly Journal of Economics, 1953)
Introduction, 97. — I. The propensity to develop pure science, 98. — II. The propensity to invent, 102. — III. The propensity to innovate, 105. — IV. The propensity to finance innovation, 108. — V. The propensity to accept innovations, 110.